Economic and Social Development under Rana Regimes in Nepal: A Historical Analysis (Patan Pragya, 2024)
This research paper explores the economic and social development in Nepal during the Rana (1846 1951) regimes. It critically analyzes the impact of political dynamics on infrastructure, industry, and social services. The Rana regime perpetuated stagnation through autocratic rule, monopolistic control, and exploitation of state resources, resulting in negligible advancement in physical infrastructure, industry, and social services. This paper aims to provide a comprehensive understanding of the obstacles to development in Nepal during the Rana Regime and the legacy they left on the nation's socio-economic landscape.